Anesthesia Dolorosa of Trigeminal Nerve, a Rare Complication of Acoustic Neuroma Surgery - Foad Elahi; Kwo Wei David Ho (Case Reports in Neurological Medicine)
Anesthesia dolorosa is an uncommon deafferentation pain that can occur after traumatic or surgical injury to the trigeminal nerve. This creates spontaneous pain signals without nociceptive stimuli. Compression of the trigeminal nerve due to acoustic neuromas or other structures near the cerebellopontine angle (CPA) can cause trigeminal neuralgia, but the occurrence of anesthesia dolorosa subsequent to acoustic tumor removal has not been described in the medical literature. We report two cases of acoustic neuroma surgery presented with anesthesia dolorosa along the trigeminal nerve distribution. The patients’ pain was managed with multidisciplinary approaches with moderate success.